METHODOLOGICAL APPROACHES TO THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES FOR DEVELOPING STUDENTS’ SPEECH COMPETENCE IN GENERAL EDUCATION SCHOOLS - Pardayeva Firuza Mamarajab qizi (American Journals, 2026)
This article provides an in-depth analysis of methodological approaches to the effective use of information and communication technologies (ICT) in the development of speech competence among general education school students. Speech competence is interpreted as a skill that must be consistently developed across all subjects, and the article explores the potential of ICT tools in enhancing listening comprehension, verbal expression, communication, argumentation, and creative speech production through interactive formats. The study substantiates, with practical examples, the application of communicative, activity-based, constructivist, differentiated, and interdisciplinary integration principles in the teaching process. It also highlights the role of purposeful integration of ICT at all stages of the lesson in activating learners’ speech and communicative engagement. Furthermore, the methodological advantages of utilizing multimodal tools such as video, audio, interactive exercises, online assessments, podcasts, presentations, and virtual communication platforms are comprehensively examined.
Keywords: Speech competence, information and communication technologies (ICT), communicative approach, activity-based learning, electronic portfolio, digital monitoring, podcast, constructivist approach, interdisciplinary integration, oral speech development.